The role of incremental innovation in micro and small businesses : qualitative study in Tetouan city of Morocco - BEN YAKOUB , Sara (Revue Internationale du Chercheur, 2024)
In a business world full of changes, several strategies have begun to be carried out by companies to remain competitive in the market, such as innovation, and to better manage innovation, it is important to distinguish innovation from minor changes in products, technologies and reorganizations. In this context, the division of innovations into incremental (incremental) and radical (basic) is important for projects. Incremental innovations sharpen already existing business areas and created by radical innovations through simple modifications of products, services or processes. The aim of this article is to highlight the role of incremental innovation in micro and small businesses in a city in northern Morocco. We conducted an interview with twelve companies in this small city. The results showed us that incremental innovation plays a key role in increasing the turnover of these companies by improving their competitive position in the market. The results showed us that despite the small size of the companies, those that applied incremental innovation were able to achieve an increase in turnover and were able to satisfy their customers and attract more potential customers.